PURIFICATION, CHARACTERIZATION AND PARTIAL STRUCTURE DETERMINATION OF NATIVE TREHALOSE-6-PHOSPHATE PHOSPHATASE FROM MAIZE GENOTYPE EC 558706 UNDER SALT STRESS CONDITION - UMESH.H.R; RAMESH.K.V (International Journal of Pharma and Bio Sciences, 2016)
The Trehalose-6-phosphate phosphatase (TPP) released trehalose is involved in diverse functions including abiotic stress tolerance in microorganisms and many plants. In our present study, maize salt stress resistant genotype EC 558706 was grown under salt stress conditions in presence of trehalase inhibitor validamycin A. The trehalose content, production and activity of TPP increased in the order of tissues as root, shoot and kernels whereas trehalase activity decreased in above tissues in the same order. A native TPP produced from maize kernels under salt stress conditions was purified using successive chromatography on sephadex G-75 and DEAE-52 columns to achieve a purification of 24 fold with a molecular mass of 40 kDa. Purified enzyme showed high phosphatase activity specific for trehalose phosphate, inactive with other sugar phosphates and Paranitrophenylphosphate. Km for trehalose phosphate was 0.3mM, and optimum pH was 7.0. Effect of different metal ions on TPP activity at various concentrations was studied. Mg2+ showed maximum activity at 2 mM. The purified enzyme was found to be stable up to 50°C. Circular dichroism spectral analysis of secondary structure of maize TPP was carried out which indicate higher beta pleated sheets showing the compactness of structure.